Fabrication of visible-light response cadmium sulfide modified superhydrophobic surface for water resource remediation. (2nd August 2021) - Cao, Yuzhe; Zhang, Hao; Yin, Yibin; Ge, Bo; Ren, Guina; Shao, Xin
Abstract: Widespread concern has been attached to the frequent occurrence of pollution by oil slicks and water-soluble pollutants in recent years. The semiconductor photocatalysis is applied to sewage treatment owing to the advantages of energy-conserving and environmental protection. However, its application is limited by the defects of not solving oil slicks and the hard recyclability. In this paper, the high specific surface area and rod-shaped CdS were prepared using template and alkali-treated methods. Next, the alkylated SiO2 and alkali-treated CdS were deposited on pure fabric by physical deposition to prepare the multifunctional superhydrophobic fabric. The specific surface area and morphology of alkali-treated CdS were tested by BET specific surface area test and field emission scanning electron microscope. Besides, oil/water separation, water contact angle, and stability test experiments were performed to determine the superhydrophobic performance. Photocatalysis degradation efficiency and cycle degradation stability of multifunctional fabric were characterized by photocatalysis degradation Rh B experiment. Consequently, the alkali-treated CdS displays a high specific surface up to 343 m 2 g −1 . The multifunctional fabric presents excellent superhydrophobic performance with the water contact angle up to 155°. Meanwhile, the water contact angle of multifunctional fabric is always over 150° under various circumstances (acid-base corrosion, soaking time at 100 °C and frictional numbers), indicating that the multifunctional fabric has excellent superhydrophobic stability. Moreover, the fabric also exhibits outstanding photocatalysis performance (the degradation efficiency is 94% after 3 cycles). Our work provides a feasible method for addressing oil slicks on water surface and degrading water-soluble pollutants with extensive application prospects in water resource remediation.